The Use of Polyvinyl Alcohol Hydrogel Implants in the Lesser Metatarsal Heads. Is it Safely Doable? A Cadaveric Study. Issue 4 (16th October 2019) - de Cesar Netto, Cesar; Godoy-Santos, Alexandre Leme; Cabe, Taylor N.; Roberts, Lauren; Harnroongroj, Thos; Fansa, Ashraf; Deland, Jonathan; Drakos, Mark
Category: Lesser Toes, Midfoot/Forefoot Introduction/Purpose: The treatment of lesser toe metatarsophalangeal joint (MTPJ) arthritis is challenging, and surgical options are scarce. The use synthetic polyvinyl alcohol hydrogel implants in the treatment of the lesser MTPJ arthritis may provide symptomatic relief. An essential technical limitation is that only 8 mm and 10 mm implants are currently available, potentially limiting their use in the lesser metatarsals. The objective of this cadaveric study was to evaluate the average dimensions of the lesser metatarsal heads using CT scans and anatomical dissections, and to perform progressive drilling of the heads, aiming to assess the largest implant dimension that would be safely introduced into the metatarsal heads, preserving an adequate bone rim and providing stability to the implant. Methods: Ten cadaveric specimens were used. Surgical procedures were performed by a single fellowship-trained foot and ankle surgeon. Height and width of all lesser metatarsals were measured on CT and during anatomic dissection. Heads of all five metatarsal were exposed. Sequential reaming of the 2nd to 4th metatarsals with 0.5 mm increments was then performed. Once a minimum 6 mm reaming was obtained, the thickness of the surrounding bone rim (dorsal, plantar, medial and lateral) was measured using a precision caliper after each reaming increment. Maximum reaming size, largest implant inserted (8 mm or 10 mm), and the presence of failure of the metatarsal head or instability of the implant were recorded. Metatarsal head sizes were compared by Wilcoxon Rank Sum Test. Multiple regression analysis evaluated measurements that influenced the maximum reaming and implant size. Correlation between CT and anatomical measurements were evaluated by intraclass correlation (ICC). P-values of less than 0.05 were considered significant. Results: CT and anatomical measurements demonstrated significant correlation (ICC range, 0.63 to 0.85). Mean values for height and width of the metatarsal heads were respectively: second (14.9 mm and 9.9 mm), third (14.8 mm and 8.8 mm), fourth (14.0 mm and 8.7 mm) and fifth (12.3 mm and 9.3 mm). All the second, third and fourth metatarsal heads could be safely drilled up to 7.5 mm, preserving an intact bone rim. At 80% of the time, the heads could be safely drilled up to 8.0 mm. Height of the metatarsal heads was the only factor to significantly influence the size of maximum reaming and implant introduced. In respectively 20%, 40% and 50% of the second, third, and fourth metatarsal heads, neither 8 mm nor 10 mm PVAH implants could be used. Conclusion: Our cadaveric study found that the even though the majority of the lesser metatarsal heads could be safely drilled up to 8 mm, the smallest PVAH implant size currently available in most countries (8 mm) could be inserted in most of the second, but only in about half of the third and fourth metatarsal heads. The remaining bone rim around inserted implants was considerably thin, usually measuring less than 1 mm. In order to optimize the use PVAH in lesser metatarsal heads, smaller implant options are needed.